Diagnosis And Treatment of Testicular Torsion - Hilmi, Tamadar; Kurniati, Intanri; Hadibrata, Exsa (CV. Jasa Sukses Abadi, 2024)
Testicular torsion is an urgent medical condition that occurs when one or both testicles experience rotation or reversal in the scrotum, thereby disrupting blood flow to the testicles. Testicular torsion usually occurs in young male patients (<25 years). If this occurs it can cause rapid testicular ischemia. Furthermore, if ischemia is not treated immediately, it can threaten the safety of the testicles and affect men's reproduction and quality of life. This disease causes 10% to 15% of acute scrotal disease in children, and causes an orchiectomy rate of 42% in boys undergoing testicular torsion surgery. This article discusses testicular torsion, including definition, symptoms, diagnosis, and management. Testicular torsion is characterized by complaints of pain, swelling and/or tenderness in the scrotum, loss of cremaster reflex, Deming's sign and Angell's sign. Apart from that, we will also discuss early detection techniques for testicular torsion, such as physical examination and ultrasound, which are very important for diagnosing this condition quickly. Testicular viability decreases significantly 6 hours after the onset of symptoms therefore early diagnosis is key. Immediate treatment with manual detorsion or surgery is necessary to restore blood flow to the testicle affected by torsion. Delay in action can cause permanent damage to the testicular tissue. Since testicular torsion is a very time-sensitive diagnosis, it may also be subject to many medicolegal challenges.